Capacity Building, Governance, and Economic Reform in Africa. (International Monetary Fund, 2001)
This volume, edited by Michel A. Dessart and Roland E. Ubogu, records the presentations made and discussions held during the Inaugural Seminar of the Joint Africa Institute (JAI). The JAI was established in Abidjan, Cote d'Ivoire, by the African Development Bank, the IMF, and the World Bank to meet the pressing training needs of the African continent. The participants discussed four main topics: the changing role of the state, governance, and new capacity requirements; the challenge of achieving macroeconomic stability in Africa; the requirement for capacity building in Africa; and the role of international financial institutions in capacity building in Africa. The seminar was held in November 1999, but the topics and recommendations of the seminar remain current and of particular importance today. The seminar was held in English and French, and both language versions are contained in this volume. 240 pp. 2001.